Kemampuan Pemecahan Masalah Serupa PISA pada Model Problem Based Learning dengan Pendekatan Flipped Classroom - Nafiah, Hidayatun; Rochmad, Rochmad; Mariani, Scolastika (Universitas Muria Kudus, 2023)
The purpose of this research was to describe the problem-solving abilities similar to PISA in the problem-based learning model with a flipped classroom approach. The low problem-solving abilities of students similar to PISA are considered essential skills needed to address current societal issues. Therefore, this issue served as the background for this research. The study utilized a descriptive qualitative research method, and data collection techniques included observation, documentation, tests, and interviews. Qualitative data analysis was employed for the analysis. The findings of this research indicate that students with low problem-solving abilities similar to PISA can understand problems well, plan solutions adequately despite some errors, perform less effectively in executing problem plans, and checking answers. Students with moderate abilities can understand problems, plan and execute solutions effectively, and check answers adequately. Meanwhile, students with high abilities can understand problems, plan and execute solutions exceptionally well, and check answers effectively.